2017
DOI: 10.1111/ejn.13488
|View full text |Cite
|
Sign up to set email alerts
|

Spectral summation and facilitation in on‐ and off‐responses for optimized representation of communication calls in mouse inferior colliculus

Abstract: Selectivity for processing of species-specific vocalizations and communication sounds has often been associated with the auditory cortex. The midbrain inferior colliculus, however, is the first center in the auditory pathways of mammals integrating acoustic information processed in separate nuclei and channels in the brainstem and, therefore, could significantly contribute to enhance the perception of species' communication sounds. Here, we used natural wriggling calls of mouse pups, which communicate need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 74 publications
(131 reference statements)
6
43
0
Order By: Relevance
“…One difference may arise from different injection areas within the shell. Considerable ascending inputs were observed when the HRP injection covered both the ICC and ICX (Aitkin et al, 1981). However, a portion of the injection area assigned to the ICC in the above study was actually the ventrolateral nucleus in the cat, which corresponds to layer 3 of the ICX in the rat (Loftus et al, 2008).…”
Section: Dominant Ascending Pathway In the Ic Shellmentioning
confidence: 85%
“…One difference may arise from different injection areas within the shell. Considerable ascending inputs were observed when the HRP injection covered both the ICC and ICX (Aitkin et al, 1981). However, a portion of the injection area assigned to the ICC in the above study was actually the ventrolateral nucleus in the cat, which corresponds to layer 3 of the ICX in the rat (Loftus et al, 2008).…”
Section: Dominant Ascending Pathway In the Ic Shellmentioning
confidence: 85%
“…Inhibition from SPON may also contribute to facilitation of IC responses to harmonically related frequencies (Akimov et al, 2017), which is a mechanism that presumably enhances the perception of natural mouse calls (Ehret and Riecke, 2002). Strong inhibition from the SPON and VNLL that marks the onset of a broadband natural sound via octopus cell activation could deactivate local interneurons, providing inhibitory side fields to IC neurons and, thereby, achieve spectral facilitation within the same neural critical band (Ehret and Merzenich, 1988; Schreiner and Langner, 1997; Akimov et al, 2017). Simultaneously, slightly temporally dispersed inhibition from SPON and VNLL may sharpen the time window of integration of the spectral peaks (Nayagam et al, 2006; Mayko et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Higher thresholds for between-channel than within-channel gap detection suggest that the mechanisms of temporal correlation across sound frequencies differ from those of discontinuity detection. Studies in both humans and mice have already indicated that sound offsets play an important role in temporal correlation across sound frequencies [36][37][38]. Thus sound-offset responses seem likely to be crucial for between-channel gap detection.…”
Section: Perceptual Roles Of Sound Offsetsmentioning
confidence: 99%